Relationship among employee’s personality traits and work motivation - Genevičiūtė-Janonienė, Giedrė; Endriulaitienė, Auksė (Psichologija, 2008)
In recent years, researchers have acknowledged that personality explains behaviour at work and predicts job performance across a wide variety of outcomes that organizations value (Barrick & Mount, 2005). Work motivation is a potential predictor of employee turnover, job satisfaction, organizational commitment, job performance and psychological well-being. Motivated employees are more likely to be creative, persistent, and productive, so managers are willing to have a highly motivated workforce. Especially work motivation is a challenge for supervisors trying to integrate into the international market using staff effectively. Knowing of personality traits and work values that help to predict work motivation allows supervisors to achieve objectives. That is why any efforts to predict individual differences of employee’s work motivation are an important research topic having both practical and theoretical implications. The objective of this study was to elucidate the personality traits that might be related to work motivation. 300 respondents (79 men and 221 women) participated in the investigation (mean age 33.70, SD = 13.09). The employees consisted of non-management personnel of various Lithuanian organizations. The subjects completed a questionnaire that included self-report measure of personality traits (Big Five Inventory; John et al., 1991), two self-repot measures of work motivation; a two-item scale was devised for assessing perceived work effectiveness. We constructed one questionnaire according to the instructions of V. Vroom’s Expectancy Theory of work motivation; another questionnaire was constructed (according to Marcinkevičiūtė, 2003; Wilson, 2005; Furnham et al., 2005) for assessing what kind of rewards employees value at their job. It was also predicted that perceived job effectiveness might contribute significantly to the model of work motivation. Contrary to the expectations and previous results, no significant relations were found among neuroticism, agreeableness, consciousness, extraversion and work motivation. Only openness to experience was positively related (p ≤ 0.034) to women’s work motivation. Path analysis showed different models of work motivation for female and male employees. Perceived job effectiveness was an important contributor to work motivation. Also, the results have shown that employees with a higher extraversion (p ≤ 0.001), higher openness to experience (p ≤ 0.000), higher conscientiousness (p ≤ 0.024) and agreeableness (p ≤ 0.021) are more motivated with internal rewards at their job. Employees with higher neuroticism are equally motivated by both external and internal rewards.